Analysis Of The Implementation Of Material Flow Cost Accounting At Pt Xyz (Car Manufacturer) - Ferdinand Munthe, Hans; Hartanti, Dwi (International Journal of Science, Technology & Management, 2024)
This research discusses implementation analysis Material Flow Cost Accounting (MFCA) at PT XYZ which is one of the car manufacturers in Indonesia. The formulation and aim of this research is to analyze potential calculations material loss and material waste produced by the method Material Flow Cost Accounting (MFCA) and evaluate management's response to management material loss and material waste from the calculations carried out. The research method used is quantitative descriptive method and case study. Resource persons in this study include: 1) Press Shop Manager 2) Body Shop Manager 3) Paint Shop Manager and 4) General Assembly Shop Manager. The data used includes primary data collected by observation and interviews. The data analysis method is carried out through five implementation stages Material Flow Cost Accounting (MFCA) in ISO 14051 and thematic analysis from sources as well as drawing conclusions and recommendations. The research results show that with implementation Material Flow Cost Accounting (MFCA) PT XYZ is able to map all material flows in detail and provide information regarding waste that can be used to increase efficiency and support environmental sustainability in the car production process.